Correlates of Postpartum Maternal Functioning in a Low-Income Obstetric Population. (March 2017) - Barkin, Jennifer L.; McKeever, Amy; Lian, Brad; Wisniewski, Stephen R.
BACKGROUND: Perinatal mental health has been characterized primarily via depression evaluation. However, there may be advantages to complementary assessment of postpartum functional status.OBJECTIVE: The purpose of this study was to examine sociodemographic and clinical factors associated with maternal functioning in low-income obstetrics patients.DESIGN: One hundred and twenty-eight women receiving postpartum obstetrical care at a large medical center in medically underserved, Middle Georgia were screened for depressive symptoms with the Edinburgh Postnatal Depression Scale. The women also completed the Barkin Index of Maternal Functioning and a sociodemographic survey. Multivariate analysis was performed to elucidate factors independently associated with maternal functioning.RESULTS: Higher Edinburgh Postnatal Depression Scale scores ( p < .0001) and being married ( p = .043) were associated with decreased maternal functioning.CONCLUSIONS: Health care providers should be cognizant of the relationship between postnatal depression and maternal functioning and its potential implications for family health.